A Contribution to the Anatomical Study of the Mandibular Premolars - Capote, T. S. O.; Barroso, R. A. A.; Pinto, S. T. P.; Conte, M. B.; Campos, J. A. D. B.; Bolini, P. D. A.; Gonçalves, M. A. (Journal of Morphological Sciences, 2018)
Introduction During the practical classes of Dental Anatomy, some students have difficulties in identifying the mandibular first premolars, especially in determining the proximal surfaces.Objective The objective of this study was to evaluate the anatomical structures of those teeth, to determine the criteria for identifying the proximal surfaces in individual teeth.Materials and Methods Two hundred mandibular first premolars belonging to 100 individuals, at the age of 18 to 25 years old and from both sexes were evaluated according to some features of the dental crown. The associations of interest were estimated using the chi-square test or Fisher's Exact Test and kappa statistic. The level of significance was 5%.Results The distal occlusal fossa (DOF) was the widest fossa (94.5%), and the distal surface constituted the proximal surface with the largest dimension (94.5%). It was found that in 60% of the teeth, the DOF was located closer to the lingual surface. The grooves from the mesial and distal occlusal fossa, toward the lingual surface, were absent in most teeth (64.5% and 91.5%, respectively).Conclusions The criteria for determining the proximal surfaces when evaluating individual first mandibular premolars should be: DOF will be the widest occlusal fossa; the proximal surface with the largest buccolingual dimension will be the distal surface. The occlusal fossa which is closer to the lingual surface may also be evaluated, being considered as the DOF. However, this should be considered the last of the three highlighted criteria, since it generates a greater margin of error in relation to the others.
Keywords: anatomy; premolar; dental crown; dental education